Respuesta :
x² - 16x + 17 = 0
x² - 16x + 8² - 8² + 17 = 0
(x - 8)² - 64 + 17 = 0
(x - 8)² - 47 = 0
-----------------------------------------------------------------------------------------
Answer: y = (x - 8)² - 47 (Answer D)
-----------------------------------------------------------------------------------------
x² - 16x + 8² - 8² + 17 = 0
(x - 8)² - 64 + 17 = 0
(x - 8)² - 47 = 0
-----------------------------------------------------------------------------------------
Answer: y = (x - 8)² - 47 (Answer D)
-----------------------------------------------------------------------------------------
Answer:
Option D is correct
[tex]y = (x-8)^-47[/tex]
Step-by-step explanation:
A quadratic equation is in the form of [tex]y=ax^2+bx+c [/tex],
then the vertex form of the quadratic equation using the completing square method is given as:
[tex]y =(x-h)^2+k[/tex] where, vertex = (h, k)
As per the statement:
Ariel completes the square for the equation: [tex]x^2-16x+17 = 0[/tex]
Using completing square method:
1.
subtract 17 from both sides we have;
[tex]x^2-16x = -17[/tex]
2.
Complete the square on the left side of the equation and balance this by adding [tex]8^2 = 64[/tex] to the right side of the equation.
then;
[tex]x^2-16x+8^2= -17+64[/tex]
Using identity rules on left side:
[tex](a-b)^2 = a^2-2ab+b^2[/tex]
then;
[tex](x-8)^2 = 47[/tex]
we can write this as:
[tex]y = (x-8)^-47[/tex]
Therefore, the equations reveals the vertex of the parabola is, [tex]y = (x-8)^-47[/tex]